Increased legs-to-total fat percentage ratio in females with a normal body mass index: A change in lifestyle or the adaptation process of the body - Boštjan Jakše; Stanislav Pinter; Uroš Godnov (Exercise and Quality of Life)
Monitoring the prevalence of obesity is of great importance for assessing lifestyle interventions aimed at preventing or reducing the health and economic burden of obesity. A sedentary Westerntype lifestyle results in an increase in the incidence of normal-weight (e.g., thin fat) obesity. In the present cross-sectional study, the regional body composition status (using a multifrequency, medically approved electrical bioimpedance monitor) of 844 Slovene adults was examined. The primary aim was to compare the leg fat percentage to total body fat percentage (LEGFAT%-toTOTFAT%) and to trunk fat percentage (TRUFAT%) (LEGFAT%-to-TRUFAT%) ratios of participants in the normal and obese body mass index (BMI) and categories according to the BMI and obesity classifications of the World Health Organization. In addition, examined how correlated with, sex, and age, according to obesity classification cut-offs. Results showed, for the whole sample, that increases by an average of 0.13% each year (ceteris paribus). However, females in the normal BMI and TOTFAT% categories, but not males, had significantly higher LEGFAT%-to-TOTFAT% and LEGFAT%-to-TRUFAT% ratios than those in the obese category. Furthermore, adjusted R2 (linear regression) showed that 82.5% of the variation in LEGFAT% was explained by variations in TOTFAT%, sex, and age. The present results indicated the increasing importance of studying the regional body composition status, especially of TRUFAT% and LEGFAT% compared with TOTFAT% (beyond the known sex differences). The clinical relevance of the increasing disproportionality in the regional body composition status of females with normal BMI and TOTFAT% needs to be further clarified.